Establishing a three-dimensional scaffold model of hepatoblastoma - Weigl, Elena Johanna; Demir, Salih; Schmid, Tanja; Hotes, Alina; Muensterer, Oliver; Kappler, Roland (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Emerging technologies such as three-dimensional (3D) cell culture and the generation of biological matrices offer exciting new possibilities in disease modelling and tumour therapy. The paucity of laboratory models for hepatoblastoma (HB), the most prevalent malignant liver tumour in children, has hampered the identification of new treatment options for HB patients. We aimed to establish a reliable 3D testing platform using liver-derived scaffolds and HB cell lines that reflect the heterogeneous biology of the disease so as to allow reproducible preclinical research and drug testing.Methods: In a sequence of physical, chemical and enzymatic decellularisation techniques mouse livers were stripped off all cellular components to obtain a 3D scaffold. HB cell lines where then seeded onto these scaffolds and cultivated for several weeks.Results: Our newly generated biological scaffolds consist of liver-specific extracellular matrix components including collagen IV and fibronectin. A cultivation of HB cell lines on these scaffolds led to the formation of 3D tumour structures by infiltration into the matrix. Analyses of drug response to standard-of-care medication for HB showed reliable reproducibility of our stocked models.Discussion: Our HB models are easy-to-handle, producible at large scale, and can be cryopreserved for ready-to-use on-demand application. Our newly generated 3D HB platform may therefore represent a faithful preclinical model for testing treatment response in precision cancer medicine.